Dominasi Ranah Kognitif dalam Evaluasi Hasil Belajar pada Implementasi Taksonomi Bloom - Khairiah Khairiah; Dwi Susanti; Dilli Salsa Fira; Muhammad Bukhori Dalimunthe; Deni Andriani (Continuous Education: Journal of Science and Research, 2026)
Assessment of learning outcomes plays a strategic role in education because it determines the extent to which learning objectives have been achieved, yet in practice it still tends to emphasize the cognitive domain more than the affective and psychomotor domains. This study aims to examine the tendency toward cognitive domain dominance in learning outcome evaluation through the implementation of Bloom's Taxonomy, to identify the factors underlying this imbalance, and to formulate implications for developing a more balanced evaluation system. A qualitative literature review approach was employed, drawing on secondary data from national and international academic journals, scholarly books, and relevant conference proceedings published mainly within the last ten years, analyzed through literature synthesis involving data reduction, thematic categorization, and conclusion drawing. The findings indicate that written tests focusing on lower-order cognitive skills such as remembering and understanding remain the predominant evaluation instruments across educational levels, including in pre-service teacher education, while affective and psychomotor assessments remain limited due to teachers' restricted understanding of Bloom's Taxonomy and the technical complexity of non-test instruments. It is concluded that cognitive dominance in evaluation practice is not merely a technical instrument choice but reflects systemic gaps in teachers' pedagogical competence and education policy orientation toward examination outcomes. These findings imply the need to strengthen teachers' assessment literacy from the pre-service stage, expand the consistent use of authentic assessment, and align education policy indicators with the principle of holistic evaluation covering the three domains proportionally.